Fears and joys of writing in the fiction of Roberto Bolaño - González, Aníbal (Literature and theology, 2024)
Roberto Bolaño’s achievement is to have written "literature about literature" that nevertheless feels profoundly alive, immediate, and exciting. This literature recognizes the intimidating and ethically dubious aspects of fiction writing, and of writing as a whole, while also imbuing its storytelling with feelings of energy and exultation. This article discusses Bolaño’s novel Distant Star and his other works, including the novel Amuleto. Drawing upon a framework of religion, secularism, and postsecularism, this article shows how Bolaño follows an ethics of writing which turns the fear of writing into a joyful and liberating activity.